'You just feel more relaxed': An Investigation of Art Room Atmosphere. (31st August 2021) - Thomson, Pat; Hall, Christine
Abstract: Art educators are increasingly interested in the affective dimensions of pedagogy. This article explores students' reports of feeling more relaxed and less stressed in the art room, data drawn from a three‐year study of thirty arts‐rich secondary schools. Drawing on recent scholarship on affect, we suggest that these feelings were in part the result of 'atmosphere' – mobile bodies in (1) a curated space, engaged with educational activities associated with (2) a signature text and pedagogy, enacted as an (3) isorhythmic practice. We suggest that these three elements of atmosphere not only help us to understand how to produce positive feelings about art, but they also have some potential for use in professional reflection on practice.